The role of autologous fat grafting in rhinoplasty - Saadoun, Rakan; Solari, Mario G.; Rubin, J. Peter (Facial plastic surgery, 2023)
Rhinoplasty is one of the most popular aesthetic surgeries worldwide and often includes grafting techniques to achieve optimal results. One of these grafting techniques is autologous fat transfer, which has been used to increase volume, camouflage irregularities, and/or improve the quality of the nasal skin-soft tissue envelope. Moreover, minimally invasive approaches for altering the nasal appearance have recently increased and become known as “liquid” or “nonsurgical rhinoplasty.” These nonsurgical approaches include altering the nasal appearance with filler injection to induce volumetric changes in lieu of extensive surgery. The use of fat grafting as a filler is favorable to achieve well-balanced aesthetic results without compromising the nasal skin-soft tissue envelope. This capability is partly because of the regenerative potential of fat grafts, serving to improve the quality of surrounding soft tissues. In contrast, commercial injectable fillers are inert. This article highlights the role of fat grafting in surgical and nonsurgical rhinoplasty to provide surgeons with an overview of the potential of these vastly abundant, biocompatible, and cost-effective grafts.
Artikel online veröffentlicht: 30. November 2022
Gesehen am 20.08.2024